Comprehensive RNA-Seq profiling of the lung transcriptome of Bashbay sheep in response to experimental Mycoplasma ovipneumoniae infection. - Zhihui Du; Yanming Sun; Jixue Wang; Haiyan Liu; Yi Yang; Ning Zhao (PLoS ONE)
The Bashbay sheep (Ovis aries), an indigenous breed of Xinjiang, China, has many excellent characteristics. It is resistant to Mycoplasma ovipneumoniae infection, the causative agent of mycoplasma ovipneumonia, a chronic respiratory disease that is harmful to the sheep industry. To date, knowledge regarding the mechanisms responsible for M. ovipneumoniae pathogenesis in scant. Herein, we report the results of transcriptome profiling of lung tissues from Bashbay sheep experimentally infected with an M. ovipneumoniae strain at 4 and 14 days post-infection, in comparison to mock-infected animals (0 d). Transcriptome profiling was performed by deep RNA sequencing, using the Illumina platform. The analysis of differentially expressed genes was performed to determine concomitant gene-specific temporal patterns of mRNA expression in the lungs after M. ovipneumoniae infection. We found 1048 differentially expressed genes (575 up-regulated, 473 down-regulated) when comparing transcriptomic data at 4 and 0 days post-infection, and 2823 (1362 up-regulated, 1461 down-regulated) when comparing 14 versus 0 days post-infection. Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that the differentially expressed genes at 4 and 14 versus 0 days post-infection were enriched in 245 and 287 pathways, respectively, and the Toll-like receptor (TLR) signaling pathway was considered most closely related to MO infection (p < 0.01). Two pathways (LAMP-TLR2/TLR6-MyD88-MKK6-AP1-IL1B and LAMP-TLR8MyD88-IRF5-RANTES) were identified based on the TLR signaling pathway from differentially expressed genes related M. ovipneumoniae infection. Gene Ontology analysis showed that differentially expressed genes in different groups were enriched for 1580 and 4561 terms, where those most closely related to M. ovipneumoniae infection are positive regulators of inflammatory responses (p < 0.01). These results could aid in understanding how M. ovipneumoniae infection progresses in the lungs and may provide useful information regarding key regulatory pathways.